Rubidium segregation at random grain boundaries in Cu(In, Ga)Se2 absorbers. (December 2017) - Schöppe, Philipp; Schönherr, Sven; Wuerz, Roland; Wisniewski, Wolfgang; Martínez-Criado, Gema; Ritzer, Maurizio; Ritter, Konrad; Ronning, Carsten; Schnohr, Claudia S.
Abstract: Solar cells based on Cu(In, Ga)Se2 absorbers are the most efficient ones among all thin film photovoltaics. The current world record efficiency was attained by applying a rubidium fluoride (RbF) post deposition treatment (PDT) to the absorber. However, it is still not clear why the introduced Rb improves the solar cell performance. In order to investigate the beneficial effect of Rb, a Cu(In, Ga)Se2 absorber was grown on a Mo coated alkali free substrate and subjected to a RbF PDT. This pure RbF PDT without any additional alkalis from the substrate leads to a strong increase in solar cell efficiency. A thin cross sectional lamella was cut out of the layer stack and investigated via a combination of electron microscopy and high resolution synchrotron based methods. This combinatory approach provides clear indications of the origin of the beneficial effect of Rb. It is evident that Rb agglomerates at detrimental random high angle grain boundaries and dislocation cores, where it likely passivates defects, which would otherwise lead to a recombination of carriers. In contrast, Rb does not agglomerate at benign Σ3 twin boundaries. Additionally, Rb segregates at the interface between the absorber and the MoSe2 layer. Graphical abstract: Highlights: Providing clear indications of the origin of the beneficial effect of Rb in CIGS. Characterization of a thin FIB-lamella via nano-XRF and electron microscopy. Rb passivates detrimental random high angle grain boundaries. Rb agglomerates at dislocation cores and at the CIGS/MoSe2 interface. Rb does not agglomerate at benign Σ3 twin boundaries.